Evaluation Of Anti-Hypertensive And Vasorelaxant Effects Of Gynura Procumbens Merr. Extracts - Iqbal, Zafar (2020)
The aims of the present study were to investigate the anti-hypertensive activity in spontaneously hypertensive rats (SHR), vasorelaxant activity in rat aortic ring preparations and blood pressure lowering activity and mechanism of action in anesthetized normotensive rats of G. procumbens extracts. Daily oral administration of GPWE has more anti-hypertensive effects in SHR compared to other extracts.